Karakterisasi Dan Modifikasi Karbon Aktif Tempurung Kelapa Sawit Dengan Asam Nitrat Untuk Menjerap Logam Besi Dan Tembaga Dalam Minyak Nilam - Harti, Retno; Allwar, Allwar; Fitri, Noor (Chemistry Department, Universitas Islam Indonesia, 2014)
Modification of activated carbon has been conducted using nitric acid (HNO3). Characterization unmodified and modified activated carbon follow type I of nitrogen adsorption isotherm showed microporous material. Langmuir surface area of 253,6 m2/g to 491,6 m2/g. Identification of fungtional groups by fourier transform infrared spectrometer and Boehm titration. An increasing oxygen group on phenol of 0,0399 meq/g to 0,1987 meq/g showed acid character. Unmodified and modified activated carbon by nitric acid used as an adsorbent. The activated carbon to adsorp metal applied Fe and Cu in Patchouli oil. The metal testing by flame - atomic absorption spectrophotometer. Maximum capacity of Fe sorption in unmodified activated carbon is 9,01 ppm/g and modified activated carbon is 12,16 ppm/g Maximum capacity of Cu sorption in unmodified activated carbon is 2,25 ppm/g and modified activated carbon is 2,85 ppm/g.